The Cooperative Learning Model of the Make a Match Method to Increase the Learning Output - Damayanti, Fransisca Dita (Universitas Sebelas Maret, 2020)
Learning is a process which built by teacher to increase student’s creative thingking, also can improve the ability of construct new knowledge. Learning outcome is one of important things to consider in learning. The learning outcomes can be formed as verbal information, intellectual skills, cognitive strategies, motoric skills, and attitudes. To get maksimum learning outcomes, the teacher must be good at designing learning by using a variety of learning models which combined by appropriate media. The cooperative learning model of the make a mach method packaged in the form of a game where students work in groups to match questions and answers in the form of cards with certain time limit. As the result we know that cooperative learning model of the make a mach method can increase the student’s learning outcomes, activeness, and cooperation. The application of this method suitable to be applied in various sciences and levels.